2010
DOI: 10.1016/j.jacc.2010.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of N-Terminal Pro–B-Type Natriuretic Peptide for Death and Cardiovascular Events in Healthy Normal and Stage A/B Heart Failure Subjects

Abstract: Objectives Our objective was to determine the prognostic value of plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) for death and cardiovascular events among subjects without risk factors for heart failure (HF), which we term healthy normal. Background Previous studies report that plasma NT-proBNP has prognostic value for cardiovascular events in the general population even in the absence of HF. It is unclear if NT-proBNP retains predictive value in healthy normal subjects. Methods We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 29 publications
8
89
0
2
Order By: Relevance
“…7,15 The difference might be explained by the fact that our cohort M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 comprised also patients with Eisenmenger syndrome and our whole group was significantly more symptomatic (19 % in NYHA class III-IV) compared to Eindhoven´s group with only 1% of patients in NYHA class III. 15 A smaller study with 49 symptomatic patients with CHD showed that both BNP and ANP have strong predictive value for the mortality in symptomatic ambulatory patients during long-term follow-up.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…7,15 The difference might be explained by the fact that our cohort M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 comprised also patients with Eisenmenger syndrome and our whole group was significantly more symptomatic (19 % in NYHA class III-IV) compared to Eindhoven´s group with only 1% of patients in NYHA class III. 15 A smaller study with 49 symptomatic patients with CHD showed that both BNP and ANP have strong predictive value for the mortality in symptomatic ambulatory patients during long-term follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8] Patients with low level of N-Terminal Pro-Brain Natriuretic Peptide (NT-proBNP) have excellent prognosis irrespective of echocardiographic findings. 2,9 For patients with advanced chronic heart failure natriuretic peptides have been accepted as a gold standard in predicting mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in advanced HF, there is controversy whether BNP concentration helps identify patients requiring heart transplantation [42,43] . Similarly, in asymptomatic individuals with HF and those in pre-HF stages, NT-proBNP failed to predict the patients who presented with clinical HF during follow-up [44] . Other limitations to the use of natriuretic peptides exist, particularly with NT-proBNP since cut-off points for assessing prognosis have not been clearly established.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The design and selection criteria of this community-based cohort study as well as the characteristics of the Olmsted County population have been previously described (20,21 ). We obtained baseline samples for hscTnI in 1843 individuals (199 of the 2042 individuals did not have samples to run for hs-cTnI), and only data from these individuals are included in this analysis.…”
Section: Study Populationmentioning
confidence: 99%